POLITENESS VIOLATION IN EFL CLASSROOM: AN ETHNOGRAPHY OF COMMUNICATION APPROACH TO CLASSROOM INTERACTION - Fitriyah Fitriyah (JOURNAL OF LANGUAGE, 2023)
In every English learning class, there must be a process of communication between lecturers and students, upholding intellectual values in communicating. Both have different social distancing that will make some politeness violations in classroom. Politeness is an important factor in human interaction, a behavior polished by relying on social conventions, institutionalized and socially evaluated. This research aims to analyze the politeness violation in EFL classroom and the most dominant of politeness violation by means of descriptive qualitative method, revealing social phenomena, using an ethnographic of communication approach.  The participants of this study are three lecturers and the students of three English classes. The study uses a qualitative descriptive method and ethnography of communication approach. The results of this study show politeness violation of tact maxim, 42,30 %, approbation maxim, 9,61 %, generosity maxim,  3,85%, modesty maxim, 13,46%, agreement maxim, 25%, and sympathy maxim, 5,76%. The most dominant politeness violation is politeness violation of tact maxim.